'A Deep Interest in Your Cause': The Inter-American Sphere of Black Abolitionism and Civil Rights. (3rd July 2021) - Belton, Lloyd
ABSTRACT: This article argues that black men and women activists from the Caribbean and South America made key contributions to the US abolitionist, civil rights and women's rights campaigns in the mid-nineteenth century. It does so by examining three case studies of Boston and New York-based activists from Brazil, Haiti and Jamaica. Using diverse primary sources from across the Americas, including court transcripts, abolitionist society minutes, and newspaper correspondence, it also demonstrates how these activists created unique inter-American dialogues on slavery, emancipation, segregation, racism, and gender between black communities in the Americas. In doing so, this article challenges current Anglo-American and North Atlantic biases in the historiography of transnational black abolitionism and civil rights, and instead shifts our attention to the inter-American sphere of black activism. Lastly, it also contributes to discussions around silence in the study of black activists during this period.